He was singin' this song : a collection of forty-eight traditional songs of the American cowboy, with words, music, pictures, and stories - Tinsley, Jim Bob (University Presses of Florida, 1981)
This book is a musical and historical narrative of the Old West, includes 48 annotated songs.